Attention-deficit/hyperactivity disorder symptoms and happiness among adults in the general population. (July 2018) - Stickley, Andrew; Koyanagi, Ai; Takahashi, Hidetoshi; Ruchkin, Vladislav; Inoue, Yosuke; Yazawa, Aki; Kamio, Yoko
Highlights: There has been little research on the association between adult ADHD and happiness. Greater ADHD symptom severity was linked to decreasing happiness. Mood instability, anxiety and depression mediated the ADHD-happiness association. Abstract: Despite an increasing focus on the role of mood and emotions in attention-deficit/hyperactivity disorder (ADHD), as yet, there has been comparatively little research on positive emotions. To address this research gap, the current study examined the association between ADHD symptoms and happiness using data from the 2007 Adult Psychiatric Morbidity Survey. The analytic sample comprised 7274 adults aged 18 and above residing in private households in England. Information was collected on ADHD symptoms using the Adult ADHD Self-Report Scale (ASRS) Screener, while happiness was assessed with a single (3-point) measure. Multivariable ordinal logistic regression analysis and a mediation analysis were performed to examine associations. Greater ADHD symptom severity was associated with higher odds for feeling less happy. Mood instability (percentage mediated 37.1%), anxiety disorder (35.6%) and depression (29.9%) were all important mediators of the association between ADHD and happiness. Given that happiness has been linked to a number of beneficial outcomes, the results of this study highlight the importance of diagnosing ADHD in adults and also of screening for and treating any comorbid psychiatric disorders in these individuals.